Bisnis Agen Pembayar Surat Pesanan ( SP ) Pada Rantai Tataniaga Tandan Buah Segar Kelapa Sawit (TBS) Ke Pabrik di Kabupaten Nagan Raya - Aswin Nasution (Jurnal Bisnis Tani, 2016)
Minister Agriculture Regulation No. 98 of 2013 allows development of palm oil mills (POM) with raw material suplies fresh fruit bunches (FFB) least 20% of its own gardens and the rest from another. This gives the chance advent of the supplier business of FFB to POM in various patterns of commerce. This study was conducted to analyze the paying agent Purchase Order (PO) in the chain patterns of commerce FFB to POM in Nagan Raya District. Results of research conducted by descriptive qualitative and quantitative shows that the generally POM raw materials in Nagan Raya Distrct can not be met from their own gardens so the suppliers FFB are needed. One of FFB commerce system chain that can be entered is the Paying Agent PO on track farmer – collecting agent - payment agent PO - holder supplier PO - POM . At the POM capacity of 30 ton FFB/hour with an estimated can to pay 30 % FFB or 115 tons FFB/day so can be obtained profits Rp. 76.400.000,-/month from turnover Rp . 533,952,000 , - up to Rp . 889,920,000 , -. Paying Agent PO business is very viable because it has a ratio Profit : Capital of 8.59 % - 14.27 % / month or 103.08 % - 171.24 % / year .